THE EFFECT OF LIQUID ORGANIC FERTILIZER (CAPRA AEGAGRUS HIRCUS) ON GROWTH ON GROWTH OF LITTLE (LACTUCA SATIVA) BY HYDROPONIC DFT SYSTEM (DEEP FLOW TECHNIQUE) - Diana, Cut Rahma; Rahmatan, Hafnati; Supriatno, Supriatno; Hasanuddin, Hasanuddin; Wardiah, Wardiah (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2020)
Research entitled